Mini literature review on the classification of intracranial calcification and the usefulness of cone beam computed tomography - Zyoud, Tawfiq Y. T.; Kabeer, Abubakar; Md Noh, Mohamad Syafeeq Faeez; Ab Hamid, Suzana; Mahmud, Rozi; Abdul Rashid, Saiful Nizam; Suppiah, Subapriya; Shamsuddin Perisamy, Rajeev; Tharek, Anas; Abdul Rahim, Ezamin (2023)
Intracranial calcification has numerous radiographic and clinical presentations; therefore, classifications and the age of the patients are very important in the detection and diagnosis of the calcifications. Interestingly, cone beam computed tomography (CBCT) provides a useful imaging technique that is very crucial in the neuro-intervention regime; although, CBCT image is faced with some drawbacks such as poor soft tissue contrast, artifacts, and noise, however, these drawbacks are taken care of with the advent of improved techniques and software algorithms that improves signal-to-noise ratio contrast.